Case report: Savolitinib induced severe adverse reactions resembling septic shock in an HIV-1–positive patient with advanced non-small cell lung cancer - Xiong, Ye; Cao, Qing; Guo, Yongzheng; Liu, Xiang; Zhu, Xueling; Dai, Bohao; Zhu, Biao (Frontiers in Pharmacology, 2023)
Savolitinib, a small-molecule inhibitor of the receptor tyrosine kinase mesenchymal-epithelial transition (MET) factor, was approved for the treatment of non-small cell lung cancer (NSCLC) by the China National Medical Products Administration in June 2021. Its safety for NSCLC treatment has been confirmed in several prospective cohort studies. Herein, we report a rare case of shock, a serious adverse event, after treatment with savolitinib in an HIV-1–positive patient with advanced NSCLC. A 38-year-old man with an 8-year history of HIV-1 positivity was diagnosed with NSCLC 5 years ago; the lung cancer recurred after surgical resection. Despite chemotherapy, immunotherapy, and targeted therapy, tumor progression continued. He received savolitinib because of MET amplification. In the first 2 weeks of savolitinib use, he developed a mild rash on his trunk. In the following month, he was hospitalized for fever and circulatory shock thrice after taking savolitinib 400 mg. He had no urticaria or eosinophilia. During the three hospitalizations, he was negative for pathogens. His condition gradually improved after treatment with antibiotics, steroids, and vasopressors. Attention should be paid to the occurrence of septic shock-like presentations when using savolitinib in HIV-1 patients with NSCLC.